(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
We review recent developments in lattice Boltzmann method for reacting flows in porous media. We present the lattice Boltzmann approaches for incompressible flow, solute transport and chemical reactions in both the pore space and at the fluid/solid interfaces. We discuss in detail the methods to update solid phase when significant mass transfer between solids and fluids is involved due to dissolution and/or precipitation. Applications in different areas are presented and perspectives of applying this method to a few important fields are discussed.